Evaluating disinfectant efficacy on mixed biofilms comprising Shiga toxigenic Escherichia coli, lactic acid bacteria, and spoilage microorganisms - Koti, Kavitha; Rodas-Gonzalez, Argenis; Nadon, Celine; McAllister, Tim; Yang, Xianqin; Narváez-Bravo, Claudia (Frontiers in Microbiology, 2024)
This study aimed to investigate the impact of temperature and the presence of other microorganisms on the susceptibility of STEC to biocides. Mature biofilms were formed at both 10°C and 25°C. An inoculum of planktonic bacteria comprising 10 6 CFU/ml of spoilage bacteria and 10 3 CFU/ml of a single E. coli strain (O157, O111, O103, and O12) was used to form mixed biofilms. The following bacterial combinations were tested: T1: Carnobacterium piscicola + Lactobacillus bulgaricus + STEC, T2: Comamonas koreensis + Raoultella terrigena + STEC, and T3: Pseudomonas aeruginosa + C. koreensis + STEC. Tested biocides included quaternary ammonium compounds (Quats), sodium hypochlorite (Shypo), sodium hydroxide (SHyd), hydrogen peroxide (HyP), and BioDestroy®-organic peroxyacetic acid (PAA). Biocides were applied to 6-day-old biofilms. Minimum Bactericidal Concentrations (MBC) and Biofilm Eradication Concentrations (BEC) were determined. Planktonic cells and single-species biofilms exhibited greater susceptibility to sanitizers (P < 0.0001). Lactobacillus and Carnobacterium were more susceptible than the rest of the tested bacteria (P < 0.0001). Single species biofilms formed by E. coli O111, O121, O157, and O45 showed resistance (100%) to Shypo sanitizer (200 ppm) at 25°C. From the most effective to the least effective, sanitizer performance on single-species biofilms was PAA > Quats > HyP > SHyd > Shypo. In multi-species biofilms, spoilage bacteria within T1, T2, and T3 biofilms showed elevated resistance to SHyd (30%), followed by quats (23.25%), HyP (15.41%), SHypo (9.70%), and BioDestroy® (3.42%) (P < 0.0001). Within T1, T2, and T3, the combined STEC strains exhibited superior survival to Quats (23.91%), followed by HyP (19.57%), SHypo (18.12%), SHyd (16.67%), and BioDestroy® (4.35%) (P < 0.0001). O157:H7-R508 strains were less tolerant to Quats and Shypo when combined with T2 and T3 (P < 0.0001). O157:H7 and O103:H2 strains in mixed biofilms T1, T2, and T3 exhibited higher biocide resistance than the weak biofilm former, O145:H2 (P < 0.0001). The study shows that STEC within multi-species biofilms' are more tolerant to disinfectants.